Background paper for the 1978 World Bank Group annual meetings - Thahane, Timothy T. (Africa Group, 1978)
The purpose of the background paper is not to duplicate the annual report of the World Bank, but to provide Governors with a quick reference on the operations of the World Bank in Africa as compared to other regions of the world.
osc 7/5/18
Loans
Keywords: World Bank